2016
DOI: 10.1016/j.fertnstert.2015.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sperm aneuploidy, sperm DNA integrity, chromatin packaging, traditional semen parameters, and recurrent pregnancy loss

Abstract: The increase in abnormal sperm parameters, sperm DNA fragmentation, nuclear chromatin decondensation, and sperm aneuploidy suggest possible causes of unexplained RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 40 publications
5
119
0
4
Order By: Relevance
“…Comparing the distribution of AB aniline blue stained sperm (Table 1, Figure 1C) of RPL patients with that of the control group, it was found that the percentage of intermediate stained spermatozoa had significantly increased along with a significant decrease in the percentage of normal protamine packaged spermatozoa (light stain). About three studies have been undertaken to measure aberrant sperm chromatin packaging by AB staining in RPL patients [Kazerooni et al 2009;Ruixue et al 2013;Zidi-Jrah et al 2016]. Our results are congruent with those obtained by these three works, which verified a lower rate of spermatozoa with normal nuclear chromatin condensation from men with spontaneous recurrent abortion compared with the control group.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Comparing the distribution of AB aniline blue stained sperm (Table 1, Figure 1C) of RPL patients with that of the control group, it was found that the percentage of intermediate stained spermatozoa had significantly increased along with a significant decrease in the percentage of normal protamine packaged spermatozoa (light stain). About three studies have been undertaken to measure aberrant sperm chromatin packaging by AB staining in RPL patients [Kazerooni et al 2009;Ruixue et al 2013;Zidi-Jrah et al 2016]. Our results are congruent with those obtained by these three works, which verified a lower rate of spermatozoa with normal nuclear chromatin condensation from men with spontaneous recurrent abortion compared with the control group.…”
Section: Resultssupporting
confidence: 89%
“…The deleterious effect of fragmented paternal DNA on embryonic viability and progression of pregnancy has been experimentally shown in mouse models [Ahmadi and Ng 1999] and similar results were also observed in human patients who opt for assisted reproductive technologies such as IVF and ICSI [Lin et al 2008;Muriel et al 2006;Robinson et al 2012;Tandara et al 2014;Tesarik et al 2004;Wdowiak et al 2015;Zhao et al 2014;Zini et al 2008]. In idiopathic cases of recurrent miscarriages too, the higher rates of sperm DNA fragmentation have been implicated, in the absence of any detectable female factor abnormality [Absalan et al 2012;Brahem et al 2011;Carrell et al 2003;Kumar et al 2012;Ramasamy et al 2015;Ribas-Maynou et al 2012;Zidi-Jrah et al 2016]. In congruence, studies have also reported interrelations between sperm chromatin alterations and early embryo post-implantation development in couples undergoing ART [ (Borini et al 2006;Seli et al 2004].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Studies of recurrent loss have reported associations with DNA fragmentation, sperm aneuploidy, sperm morphology, and motility. (8, 23, 26) However, these prior studies have relied upon a case-control design. A key limitation of the case control design is that the control group is not at risk for loss, as by definition their pregnancy went to term.…”
Section: Discussionmentioning
confidence: 99%
“…Zidi-Draj et al reported higher levels of sperm immotility, abnormal morphology, and elevated sperm DNA fragmentation in men with RPL. (7) Elevated levels of sperm aneuploidy have also been reported among men from couples with RPL. (8) However, as these studies rely on case control design with fertile couples serving as controls, prospective studies are required to confirm the reported associations.…”
Section: Introductionmentioning
confidence: 99%